Southern theories and decolonial childhood studies. (August 2022) - Abebe, Tatek; Dar, Anandini; Lyså, Ida M
This special issue contributes insights into ongoing debates on the politics and ethics of knowledge production in "global" childhood studies by decentering dominant, northern-centric models of childhood and using southern epistemologies. We contest the ways in which most of the world's children have their experiences and contexts interpreted through the theoretical canons, vernaculars and institutions of northern academia. Drawing on studies that deploy indigenous, decolonial and postcolonial perspectives on the study of childhood and children in different temporal moments and spatial contexts of Africa, Latin America and South Asia, authors of papers aim to push the boundaries for ways of knowing children and doing childhood studies through cross-disciplinary, generative south-north and south-south encounters. The special issue critically engages with questions of epistemic plurality and bottom-up theorization of research with globally southern children, to both rectify the onto-epistemological imbalance in childhood studies and reinscribe indigenous knowledge systems that have received limited attention in this field thus far.